Videojuego violento y su incidencia en el estado emocional de un niño de 7 años de edad en la Unidad Educativa Adolfo María Astudillo del cantón Babahoyo - Garzón Jaime, Nathaly Jamilet (2021)
This case study is developed due to the lived experience as a result of the pre-professional practices in the Adolfo María Astudillo educational unit, on behalf of a fourth-year elementary school boy who is 7 years old and has pathologies related to excessive use of video games with content of violence, triggered by the use of mobile devices, connectivity, lack of control by their parents or legal guardian, among others. Therefore, a scientific - experimental investigation is carried out, in order to obtain specific data, through the structure of the DSM-5 that provide clear specifications to identify internet gaming disorders, the process is developed through the complex examination modality, part practice with the direction to the line of research such as: prevention, diagnosis, evaluation and psychotherapeutic treatment in the clinical field in connection with the subline: change processes and problems associated with addictive behaviors, which allow generating information in relation to the identification of problems, causes and effects, as well as highlighting the importance of the role of parents in the physical and emotional growth of minors, even considering that the modern era and current technology have fractured the family structure as a fundamental basis in society.